A Governance Model for Music Performances to Enhance Audience Participation: A Practice-Based Study of Music Event Production in Arts Education Contexts - Yade Surayya; Nora Anggraini; Fahmi Marh; Md Jais Ismail (Pascasarjana Institut Seni Indonesia Padang Panjang, 2026)
This study aims to formulate a music performance governance model to enhance audience participation through a practicebased approach. The research is motivated by the persistent issue of low audience attendance at artistic performances, despite their high artistic quality, indicating that effective governance plays a crucial role in performance success. A qualitative approach was employed using a practicebased research design with a case study strategy. The study was conducted within the context of music performance practices in arts education institutions over a threeyear period (2023–2025). Data were collected through participatory observation, indepth interviews with 15 informants comprising managerial teams, artistic teams, and audience members, as well as performance documentation. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that performance governance has a more decisive influence on audience participation than artistic quality alone. Successful performances are achieved through the integration of audienceoriented strategic planning, effective production organization, highquality performance execution, and continuous evaluation. Furthermore, intensive promotional strategies and the involvement of popular artistic figures significantly increase audience appeal. This study proposes a cyclical and applicable music performance governance model that contributes to the development of performing arts management and offers a practical framework for arts education and performance industries.